2011
DOI: 10.1017/s030500091100016x
|View full text |Cite
|
Sign up to set email alerts
|

The shape-bias in Spanish-speaking children and its relationship to vocabulary

Abstract: Considerable research has demonstrated that English-speaking children extend nouns on the basis of shape. Here we asked whether the development of this bias is influenced by the structure of a child's primary language. We tested English- and Spanish-speaking children between the ages of 1 ; 10 and 3 ; 4 in a novel noun generalization task. Results showed that English learners demonstrated a robust shape-bias, whereas Spanish learners did not. Further, English-speaking children produced more shape-based nouns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…The participants were children who were monolingual speakers of three different languages: English, Spanish and Japanese. These languages differ in how they individuate nouns; past research has shown cross-language differences in some aspects of the shape bias for children learning these languages (Colunga, Smith, & Gassar, 2009; Gathercole & Min, 1997; Hahn & Cantrell, 2012; Imai & Gentner, 1997; Yoshida & Smith, 2003). Thus, the comparison of children speaking these different languages provides a strong test of the universality of the effect of set size on individuation and attention to shape; if the effect is supported by basic perceptual and cognitive processes then set size should affect speakers across languages with varying ways of marking individuation.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were children who were monolingual speakers of three different languages: English, Spanish and Japanese. These languages differ in how they individuate nouns; past research has shown cross-language differences in some aspects of the shape bias for children learning these languages (Colunga, Smith, & Gassar, 2009; Gathercole & Min, 1997; Hahn & Cantrell, 2012; Imai & Gentner, 1997; Yoshida & Smith, 2003). Thus, the comparison of children speaking these different languages provides a strong test of the universality of the effect of set size on individuation and attention to shape; if the effect is supported by basic perceptual and cognitive processes then set size should affect speakers across languages with varying ways of marking individuation.…”
Section: Methodsmentioning
confidence: 99%
“…What the task does require is knowledge that shape and not color or size or texture is most likely the relevant dimension for determining category membership. This knowledge and the ability to selectively attend to shape in this task appear relevant to object name learning because 18- to 30-month-old children’s performances in the shape bias task are strongly related to their current noun vocabulary size (Smith, 1995; Gershkoff-Stowe and Smith, 2004; Perry and Samuelson, 2011; Hahn and Cantrell, 2012). More critically, the strength of the shape bias during this period also predicts children’s future vocabulary growth rate (Samuelson, 2002; Smith et al, 2002; Gershkoff-Stowe and Smith, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This “shape bias” is thought to arise because children’s early English vocabularies are dominated by object names that refer to solid things belonging to categories organized by shape (e.g., ball, cup). The shape bias is also observed in some other languages, though not as robustly (e.g., Gathercole & Min, 1997; Hahn & Cantrell, 2012; Waxman, Senghas, & Benveniste, 1997). …”
Section: Children’s Early Vocabularies and Spaced Learningmentioning
confidence: 75%